PRODUKSI EPIGALLOCATECHIN GALLATE PADA KULTUR IN VITRO KALUS CAMELLIA SINENSIS SEBAGAI KANDIDAT PANGAN FUNGSIONAL - Basuki, Sutini (UPN VETERAN JAWA TIMUR, 2011)
Epigallocatechin gallate (EGCG) were secondary metabolite in tea (Camellia sinenis) as anti obecity dan degenerative syndrom. EGCG in tea act as bioactive by hydroxyl group and galoil that could act as functional food substitute. Problem to find epigallocatechin gallate from tea were season dependent, need a large area, and low productivity. By these mean epigallocatechin gallate production by in vitro culture. These technique could overcaming all that problem above. General purpose of these research were to find invitro EGCG production technique. Method to gain these purpose were : (1) Callus induction by explant sprout tea leaves in media with many variance grown culture (2) Sub culture callus by using same media in induction method (3) qualitative analisys EGCG callus compound. Result of these research; callus hand retention time (tR) on High Performance Liquid Chromatography for 6 minutes, same as EGCG standart. EGCG had potential as aditive functional food and baverage that had astringent or bitter tasteKey words : Epigallocatechin gallate, HPLC, retention time, Camellia sinensis